Structure‐Based System Dynamics Analysis of Engineering Design Processes. Issue 3 (14th September 2016) - Kasperek, Daniel; Schenk, Daniel; Kreimeyer, Matthias; Maurer, Maik; Lindemann, Udo
ABSTRACT: The dynamic process behavior of Engineering Design Processes (EDPs) needs to be understood in order to distribute resources appropriately as well as for cost and schedule calculation. Currently, structural and behavioral modeling approaches are used in the context of EDP management. In many use cases, it is essential to have at hand both the static structural view and the dynamic behavioral one. Currently, however, the two modeling approaches cannot be sufficiently combined. Within this work, a framework for the structure‐based System Dynamics analysis of EDPs is presented. It uses structural models as a basis for constructing System Dynamics models to simulate the process behavior and thereby supports understanding the correlation of process structure and behavior. This framework was iteratively developed by conducting case studies and consists of three layers, a five‐step procedure and special support for the transformation of the models. For the validation, a subset of the design process at a large German commercial vehicle manufacturer has been chosen. Based on the application of the framework during a six‐month project at the company, the industrial experts rated the framework as beneficial for the purpose of optimizing EDPs. Furthermore, they stated that the transparent representation of the sequence of the process, influencing factors and control variables in combination with the quantitative data had improved their understanding of the overall process.